Numerical Study of Airflow Effect on Temperature - Harun, Mohammad Fazlan; Mat Isa, Norasikin (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Thermal comfort can be defined as the state in which an individual felt a sense of well-being in relation to the thermal conditions in an occupied space. The variety of personal preferences of individuals in feeling the thermal condition makes a definitive definition of thermal comfort difficult to describe. Computational fluid dynamics has now made it possible to simulate the airflow behaviour using simulation applications. This study is capable to provide an understanding of the airflow behaviour in air conditioning room. Upon completion of this study, the airflow of the air conditioning system can be simulated. It is expected to determine the possibility whether the velocity of airflow has a significance change on the air distribution thus affecting the thermal conditions. CFD ANSYS Fluent simulation method was used to simulate and analyze the velocity and temperature distribution in the test rig which is a room. There are three value of air velocity that have been manipulated in this simulation which are 0.2 m/s, 0.5 m/s and 0.9 m/s. The result obtained show that all velocity streamline shows a similar pattern except that with higher velocity of air supply at inlet, the more streamline created thus can cover the test rig more comprehensively. In term of air velocity distribution, the air velocity decreases as it goes from the upper horizontal plane to the lower horizontal plane, as seen by the velocity contour formed. This is due to the opening of the inlet, which is located at the top-centre of the domain. As a result, the areas with the highest air velocity are unquestionably those closest to the inlet. Even while the temperature contour is noticeably different in colours, indicating that there is still a variation along the temperature value on the plane, the difference is still very little and insignificance differ only around 0.1 Celsius. Optimum placement of inlet and outlet causes temperature distribution to be uniform throughout the room, resulting in cold air spreading evenly.